The Dynamics of Antibody Titres Against SARS-CoV-2 in Vaccinated Healthcare Workers: A Systemic Literature Review - Vilija Gurkšnienė; Tadas Alčauskas; Fausta Majauskaitė; Ligita Jančorienė (Vaccines)
Background and Objectives: Given that COVID-19 vaccination is a relatively recent development, particularly when compared to immunisation against other diseases, it is crucial to assess its efficacy in vaccinated populations. This literature review analysed studies that monitored antibody titres against SARS-CoV-2 in healthcare workers who received COVID-19 vaccines. Methods: Using the PICO (Population, Intervention, Comparators, Outcomes) model recommended in the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines we included 43 publications which analyse antibody dynamics following primary vaccination, the effects of booster doses, and the influence of factors such as COVID-19C infection, age, and sex on antibody kinetics. Results: All the studies demonstrated a strong immunogenic response to the vaccines. Re-gardless of the vaccine used, over 95% of the pre-vaccination seronegative population be-came seropositive in all studies. Depending on the sampling intervals provided by the re-searchers, antibody levels were quantitatively highest during the first three months after vaccination, but levels inevitably declined over time. The monthly decline in antibodies observed in all these studies highlighted the necessity for booster doses. Studies analysing the impact of revaccination on antibody dynamics have confirmed that revaccination is an effective tool to boost humoral immunity against SARS-CoV-2. An-tibodies appear to persist for a longer period of time after revaccination, although they are subject to similar factors influencing antibody dynamics, such as age, comorbidities, and exposure to COVID-19. In addition, heterogeneous revaccination strategies have been shown to be more effective than homogeneous revaccination. Conclusions: Our review demonstrated that antibody levels against SARS-CoV-2 inevitably decline after vaccination, leaving the question of ongoing booster strategies open. The studies reviewed provided evidence of the effectiveness of booster vaccination, despite differences in age, sex, and prior COVID-19 infection. This suggests that repeated vaccination remains a highly effective method for mitigating the continued threat posed by COVID-19.